Effect of Osmo-convective Drying on Quality of Litchi - Kumar, Vishal; Kumar, Gunjan; Sharma, P D (Journal of Agricultural Engineering, 2009)
Osmotic dehydration has been proposed in combination with air drying to improve quality attributes of air dried litchi fruit pieces as a pre-treatment for further drying. The influence of the osmotic step and of the syrup and salt composition on the chemicalâ€“physical properties, and colour changes of osmo-air-dehydrated (litchi chinensis Sonn.) cubes was studied. The effects of variations in sucrose (50% and 60% w/w) and salt concentrations (10% w/w), solution temperature, and length of immersion time on the moisture removal of the product and its organoleptic characteristics were analyzed. About 80% of water loss occurred between 120-240 min of osmosis for most of the conditions. After osmotic treatment, the fruits were dried in a tray dryer at 70ÂºC for 10 h. Osmotic treatment was responsible for increasing drying rate in a subsequent convective tray drying.